"National Dialogue and Societal Security in Iraq after 2003: An Analytical Approach in Light of International Interactions" (قضايا سياسية, 2025)
National dialogue is a key tool for establishing the foundations of peaceful coexistence, especially in societies suffering from sectarian and political conflicts. After 2003, Iraq underwent significant transformations in its political, social, and security structures, which led to complex challenges directly affecting community security and stability.In this context, national dialogue emerged as a strategic mechanism to address societal divisions. However, a lack of trust among political actors and the prioritization of narrow interests over national interests hindered many dialogue initiatives. Several initiatives were launched, focusing on critical issues such as power distribution, resource management, and national reconciliation. Despite these efforts, political obstacles and the absence of commitment to implementing dialogue outcomes prevented these initiatives from achieving their intended goals.